Effective excitons separation in starfish Bi2S3/TiO2 nanostructures for enhanced hydrogen production. (December 2022) - NavakoteswaraRao, V.; Shankar, M.V.; Yang, B.L.; Ahn, C.W.; Yang, J.M.
Abstract: Water Splitting into gaseous hydrogen and oxygen through photocatalytic and electrocatalytic methods are notable alternative energy resources as it operates under ambient temperature/pressure that showed enormous potential to meet the clean energy demands. Hierarchical decoration of nano-size TiO2 on Bi2 S3 (Bi2 S3 @TiO2 ) having starfish morphology with a varied amount of TiO2 are synthesized by one-pot hydrothermal method both semiconducting and catalytic properties of pristine and Bi2 S3 @TiO2 hierarchical nanostructures are thoroughly characterized and discussed by using structural, optical, morphological, electronic, surface and bulk elemental composition analysis. Heterojunction formed between Bi2 S3 and TiO2 promotes suppression of photo charge carrier recombination and facilitated fast transportation of charge carriers in turn promoted oxidation and reduction reactions at catalytic active sites. The optimized photocatalyst Bi2 S3 @TiO2 displayed a large surface area of 38.6 m 2 g −1 and plenty of catalytic active sites facilitated a high turn-over frequency of 0.085 cm −1 . Further, the optimal experimental conditions, a high rate of H2 evolution of 44.1 mmol h −1 g −1 cat under UV–visible light to the hydrogen conversion efficiency was calculated as 21.7%. Consequently, the electrochemical measurements of the Bi2 S3 @TiO2 a significantly HER overpotential of 222/332 mV to achieve a current density of 20/50 mA cm −2 . As a result, enhanced efficiency of Bi2 S3 @TiO2 /NF is demonstrated for H2 evolution in an alkaline medium. The overall water splitting performance is attributed to available plenty of catalytic active sites. Thus, the prepared composite showed enhanced stability for prolonged usage for 50 h of light irradiation. These results will open up opportunities to develop low-cost and earth-abundant efficient electrode materials for multi-functional applications. Graphical abstract: Image 1 Highlights: The hierarchical photocatalyst showed a high rate of H2 generation is 44.1 mmol.h −1 .g −1 cat The optimized material is exhibited 3.2 folds greater than pristine photocatalysts. Bi2 S3 @TiO2 hierarchal nanostructures existed UTH-21.7%. Fabricated electrocatalyst displayed a significant HER performance of 15.2 mA cm −2 .